HOW TO RAISE AN EMOTIONALLY HEALTHY, HAPPY CHILD hOW TO PREVENT YOUR CHILD FROM BECOMING A NEUROTIC ADULT - ELLIS ALBERT; Sandra Moseley and Wolfe Janet L (The Institute of Rational Living , Inc. United Status of America, 1968)
The book about Neurotics child, Helping Children in overcome fears , anxieties, problems of achievement, overcome hostility, to become self disciplined and many more....